B cells from patients with rheumatoid arthritis show conserved CD39-mediated regulatory function and increased CD39 expression after positive response to therapy - Zacca, Estefanía (2021)
Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by progressive joint destruction associated with increased pro-inflammatory mediators. In inflammatory microenvironments, exogenous ATP (eATP) is hydrolyzed to adenosine, which exerts immunosuppressive effects, by the consecutive action of the ectonucleotidases CD39 and CD73. Mature B cells constitutively express both ectonucleotidases, converting these cells to potential suppressors. Here, we assessed CD39 and CD73 expression on B cells from treated or untreated patients with RA. Neither the frequency of CD73+CD39+ and CD73-CD39+ B cell subsets nor the levels of CD73 and CD39 expression on B cells from untreated or treated RA patients showed significant changes in comparison to healthy controls (HC). CpG+IL-2-stimulated B cells from HC or untreated RA patients increased their CD39 expression, and suppressed CD4+ and CD8+ T cell proliferation and intracellular TNF-production. A CD39 inhibitor significantly restored proliferation and TNF-producing capacity in CD4+ T cells, but not in CD8+ T cells, from HC and untreated RA patients, indicating that B cells from untreated RA patients conserved CD39-mediated regulatory function. Good responder patients to therapy (R-RA) exhibited an increased CD39 but not CD73 expression on B cells after treatment, while most of the non-responder (NR) patients showed a reduction in ectoenzyme expression. The positive changes of CD39 expression on B cells exhibited a negative correlation with disease activity and rheumatoid factor levels. Our results suggest modulating the ectoenzymes/ADO pathway as a potential therapy target for improving the course of RA.